Optimization of environmental parameters for Nannochloropsis salina growth and lipid content using the response surface method and invading organisms - Bartley, Meridith L; Boeing, Wiebke J; Daniel, David; Dungan, Barry N; Schaub, Tanner (Journal of applied phycology, 2016)
Algae biofuel has the potential to replace fossil fuels. However, cultivation and productivity of target algae need improvement, while controlling undesired organisms that can lower the efficiency of production systems. A central composite design and response surface model were utilized to predict cultivation optima of marine microalga, Nannochloropsis salina, under a suite of environmental parameters. The effects of salinity, pH, and temperature and their interactions were studied on maximum sustainable yield (MSY, a measure for biomass productivity), lipid content of N. salina, and invading organisms. Five different levels of each environmental predictor variable were tested. The environmental factors were kept within ranges that had previously been determined to allow positive N. salina growth (14.5–45.5 PSU; pH 6.3–9.7; 11–29 °C). The models created for this experiment showed that N. salina’s MSY and lipid content are not strongly affected over the broad range of salinity and temperature values. Calculated optima levels were 28 PSU/20 °C for MSY and 14.5 PSU/20 °C for lipid accumulation, but neither value significantly influenced the model. However, pH was the most important factor to influence algae productivity, and pH optimum was estimated around 8. Both MSY and lipid content were strongly reduced when pH deviated from the optimum. Occurrence of invading organisms seemed stochastic, and none of the environmental factors studied significantly influenced abundance. In conclusion, pH should be kept around 8 for maximum productivity of N. salina. Temperature and salinity should be kept around 20 °C and 28 PSU; however, moderate variations are not too much of a concern and might enhance lipid content of N. salina.